An Overview of Gillnet and Trammel Net Size Selectivity in the Turkish Inland Fisheries - Cilbiz, Mehmet; Atessahin, Tuncay (Istanbul Univ Press, Fac Aquatic Sciences, 2024)
This study compiled and remodelled length selectivity studies carried out on fish caught with gill nets and trammel nets in the inland fishery in T & uuml;rkiye and evaluated them based on both the initial reproduction length and minimum landing size of species. The required data for the study were obtained through a literature review. 34 selectivity studies in total were identified, and 26 (76.5%) of them were carried out with gill net while the remaining 8 (23.5%) were conducted with trammel net. 24 of the studies were carried out according to SELECT (Share Each Length-class's Catch Total) and 10 of them according to Holt (1963). In conclusion, it was found that minimum conservation reference size ( MCRS ) values determined by the Ministry in the inland fishery in T & uuml;rkiye were substantially greater than lengths at first maturity ( LFMs ) of species and that fishing gears used for fishing typically tended to fish mature individuals above MCRS . The major problem in terms of management is that different ideal mesh sizes are applied to different fish species that are in the same fishing place. Set nets with an ideal -mesh size for a species has a potential of catching individuals below LFM of other species in the same fishing grounds. It is thought that this problem can only be resolved with the Ecosystem Approach to Fisheries Management ( EAFm ).
Keywords: Inland fisheries; Length at first maturity; Minimum conservation reference size; Small scale fisheries; Sustainable fishery